Utilizing the theory of planned behavior to predict COVID-19 vaccination intention: A structural equational modeling approach - Huy Nhuong Bui; Cong Doanh Duong; Van Quang Nguyen; Ngoc Xuan Vu; Son Tung Ha; Trung Thanh Le; Trong Nghia Vu (Heliyon, 2023)
It is essential to achieve herd immunity in order to control the COVID-19 pandemic, and this requires a high level of vaccination rate. Despite the importance of vaccination, hesitancy and unwillingness in receiving the COVID-19 vaccine still exists. It is therefore crucial to comprehend the intentions of adults regarding COVID-19 vaccination, which is beneficial for establishing community immunity and an efficient future pandemic response. An online survey was administered to 2722 adults in Vietnam. Cronbach's alpha, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) were used to test the reliability and validity of the developed scales. Then, structural equational modeling (SEM) was employed to test correlations. This study found that favorable attitudes toward COVID-19 vaccines played the most important role in shaping adults' intention to receive these vaccines, followed by perceived behavioral control, perceived benefits of COVID-19 vaccines, and subjective norms. Concurrently, all three core dimensions of the theory of planned behavior mediated the link between the perceived benefits of COVID-19 vaccines and the intention to receive them. Also, there were significant differences between males and females in the way they formed this intention. The findings of this study offer valuable guidance for practitioners on how to encourage adults to receive COVID-19 vaccinations, as well as how to limit the transmission of the COVID-19 virus.